Peran Manajemen Kurikulum dalam Mewujudkan Pendidikaan Yang Berkelanjutan - Dinda Bastari; Lusiana Putri Lubis; Maulatul Fanisa; Merika Setiawati; Hendri Budi Uatama (CV. ITTC INDONESIA, 2025)
Sustainable education is a crucial approach in shaping a competent and environmentally conscious generation. This article explores various aspects of sustainable education, including its definition, principles, challenges, the role of curriculum management, strategies, benefits, and implementation. According to Mujiati et al. (2023), sustainable education integrates academic knowledge with moral character. However, challenges such as limited resources and lack of understanding still persist (Fathurrochman, 2017). In the context of curriculum management, effective strategies include teacher training, the development of responsive curricula, and continuous evaluation. The benefits include improved education quality and stronger collaboration among stakeholders. Practical examples of implementation demonstrate how schools can integrate community-based projects and technology into the learning process to achieve the goals of sustainable education.